SOCIAL INTEGRATION IN A MULTICULTURAL SOCIETY FROM THE PERSPECTIVE OF LOCAL WISDOM VALUES - Muhammad Natsir; Arief Fahmi Lubis; Made Ayu Anggreni (Adisam Publisher, 2026)
This literature research explores social integration in multicultural societies from the perspective of local wisdom values. Focusing on how traditional and local values can contribute to social harmony and cohesion in culturally diverse environments, this study identifies various critical factors that influence the success of such integration. Through in- depth analysis, it was found that active community involvement, visionary leadership roles, as well as education and preservation of local cultural values are the main elements in supporting effective social integration. This research also highlights the importance of adapting local wisdom in a modern context, synergy between sectors, and adequate documentation for the dissemination of cultural knowledge. Enforcement of customary law in synergy with national law and promotion of cultural interaction through cross-cultural programs have been proven to strengthen social networks and bridge cultural differences. Case studies from various regions show that a holistic and structured approach in applying local wisdom values can increase social cohesion, strengthen a sense of togetherness, and minimize conflict in a multicultural society. The results of this research emphasize the importance of integration between local values and modern strategies to create a harmonious and sustainable society.